Local government debt, resource misallocation, and green total factor productivity in China - Deng, Guangjun; Zhou, Canwei; Wang, Dingxing; Zhou, Weihan (Frontiers in Environmental Science, 2023)
Although China has implemented numerous environmental governance polices to realize green development, no significant changes have been achieved in reality. To understand the underlying reasons, we relate green development to the debt-driven model by the local government. Using the total debt data of prefecture-level cities in China from 2007 to 2013, we analyze the effects of debt expansion through a two-way fixed effect model. Results imply that the expansion of local government debt will inhibit green total factor productivity, but there are differences between long-term and short-term debts. Further analysis shows that local government debt will affect capital misallocation and also finds that an increase in local government debt will increase urban carbon emissions. This study recommends that the Chinese government should further decrease debt size and improve investment effectiveness to achieve high-quality development.